The influence of cultural background of test participants and test facilitators in online product evaluation. Issue 111 (March 2018) - Sauer, Juergen; Sonderegger, Andreas; Hoyos Álvarez, Mariana A.
Highlights: The study carried out the first cross-cultural comparison of groups of European and Latin American users in usability testing. It was the first study that examined cultural mismatch by using a full factorial design. The study used a large range of outcome measures, including performance, perceived usability and qualitative user comments. Swiss users provided more critical usability ratings and showed higher performance than Colombian users. Abstract: Using online usability testing as a methodological approach, an experiment was carried out in two socio-cultural regions (Switzerland and Colombia) to examine how test outcomes are influenced by culture. Employing a 2 × 2 × 2 design, socio-cultural background (Switzerland / Colombia), cultural match between test facilitator and participant (mismatch / match) and product price (high / low) were manipulated. Two hundred and two participants were asked to carry out various tasks of mobile phone users. Performance and perceived usability were measured. Qualitative comments on usability were also recorded. The results showed that Swiss users were more critical in their subjective usability ratings and made more negative comments about the product's usability than their Colombian counterparts did. There were no noteworthy effects of product price and cultural match. Future work needs to determine whether the influence of cultural match is negligible if online testing is used.